Effect of three organic plant powder extracts on storability and quality of maize grains - Kudozia, Emmanuel Gameli (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of Master of Philosophy (M. Phil. Postharvest Technology) degree, 2014